Crash and burn [compact disc, unabridged] - Lange, Artie, 1967- (Tantor Media, Inc., 2013)
The veteran comedian and radio personality turns an unflinching eye and his signature wit on his perilous descent into drug addiction, life-threatening depression, and ultimately, his recovery. The story of his life is as shocking as it is funny, ever tempered by his characteristic humor, self-awareness, and inimitable way with words.